Visiting the forced visitors: Critical and decentered approach to Global Citizenship Education as an inclusive educational response to forced youth migration - Harðardóttir, Eva; Jónsson, Ólafur Páll (JSSE - Journal of Social Science Education, 2021)
Migrant and refugee youth face complex challenges pertaining to educational and social inclusion in Europe and international contexts. Global Citizenship Education (GCE) has gained increased prevalence as an educational response to globalizing processes such as forced migration and resulting cultural diversity. It is argued that a critical and decentered model of GCE can be applied as an inclusive educational response to refugee youth within national educational settings. Visual and participatory educational practices emphasizing the role of the teacher as a 'visitor' are presented and discussed. Purpose: To explore the role and possibilities of Global Citizenship Education (GCE) in attending to neglected aspects of inclusive education when responding to forced youth migration in Europe. Approach: We discuss different approaches to GCE within the literature, their implications for refugee students within national educational settings and give an example of how critical GCE can be practiced in education. Finding: Drawing on theoretical work of John Dewey and Hannah Arendt, in conjunction with more recent theoretical work on global citizenship within education, we argue that a critical and decentered model of GCE is important to support processes of inclusion and citizenship for refugee youth within national educational settings. Implications: We apply and discuss the suggested theoretical approach in relation to pedagogical practices developed as a part of an ongoing research project on irregular processes of inclusion and citizenship for migrant and refugee youth in Iceland, Norway, and the UK.